2018
DOI: 10.1093/jtm/tax097
|View full text |Cite
|
Sign up to set email alerts
|

Business travel-associated illness: a GeoSentinel analysis†

Abstract: Diarrheal illness was a major cause of morbidity. Malaria contributed substantial morbidity and mortality, particularly among business travelers to sub-Saharan Africa. Underuse or non-use of chemoprophylaxis contributed to malaria cases. Deaths in business travelers could be reduced by improving adherence to malaria chemoprophylaxis and targeted vaccination for vaccine-preventable diseases. Pre-travel advice is indicated for business travelers and is currently under-utilized and needs improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…GeoSentinel is a global network of travel medicine providers that see ill returned travelers [12], and it set up to assess destination specific risks [13], risks by purpose of travel [14][15][16][17], and by diseases [18][19][20][21][22] and time trends [23]. Yellow fever was not reported in a descriptive analysis of life-threatening tropical diseases among 82,825 ill western travelers reported to GeoSentinel from June of 1996 to August of 2011 [24].…”
Section: Risk In Travelersmentioning
confidence: 99%
“…GeoSentinel is a global network of travel medicine providers that see ill returned travelers [12], and it set up to assess destination specific risks [13], risks by purpose of travel [14][15][16][17], and by diseases [18][19][20][21][22] and time trends [23]. Yellow fever was not reported in a descriptive analysis of life-threatening tropical diseases among 82,825 ill western travelers reported to GeoSentinel from June of 1996 to August of 2011 [24].…”
Section: Risk In Travelersmentioning
confidence: 99%
“…1 Studies have demonstrated low rates of insect repellent uti lization, vaccine series completion, and proper utilization of malaria prophylaxis among travel ers. 13, [41][42][43] To what extent VFR travelers tighten their selection of water sources and use of hand washing in cholera zones, or defer ritualistic fu neral practices in regions with Ebola virus, for in stance, is unknown. Nonetheless, tailored advice relevant to emerging infectious diseases events should be incorporated along with usual guid ance on maintaining wellness while traveling, when relevant to the itinerary.…”
Section: Fever In a Traveler: A Clinical Syndrome In Contextmentioning
confidence: 99%
“…As businesses reopen and re-establish a new normal, business travel needs fresh assessments. 3 The COVID-19 pandemic will inevitably lead to redefining essential travel. The crisis provides an opportunity to stimulate expertise among travel medicine clinicians, to utilize and promote skills and knowledge to assist in the recovery and reopening of the economy.…”
Section: Introductionmentioning
confidence: 99%